Synthesis and characterization of novel tetra- and octa-triethyleneoxysulfanyl substituted phthalocyanines forming lyotropic mesophases - Dabak, S; Ahsen, V; Heinemann, F; Zugenmaier, P (Gordon Breach Sci Publ Ltd, 2000)
Metal-free phthalocyanines and nickel phthalocyanines carrying four or eight oligo(ethyleneoxy)thia groups on peripheral positions have been synthesized from new phthalonitrile derivatives. These phthalocyanine derivatives were characterized both thermotropic and lyotropic mesophases by DSC and X-ray.
Keywords: phthalocyanines; soluble; Oligo(ethyleneoxy)thia; Liquid crystal; thermotropic and lyotropic mesophases